"Heroisch-komisches Singspiel" und "Ägyptische Mysterien" in Mozarts und Schikaneders Zauberflöte - Assmann, Jan (Musik & Ästhetik, 2017)
»Heroic-Comic Singspiel« and »Egyptian Mysteries« in Mozart and Schikaneder’s Magic Flute - Mozart and Schikaneder’s opera The Magic Flute is a work of completely unique complexity. The context of the plot quickly became incomprehensible, and is still widely considered a mystery today. One possible solution would be that it brings together entirely different conceptions. Schikaneder evidently had a »heroic-comic opera« in mind, the most popular genre in late 18th-century Vienna, based on fairy tales from Wieland’s collection Dschinnistan. Mozart, on the other hand, may have planned to stage the »Egyptian mysteries«, the object of years of research by the Vienna lodge »Zur wahren Eintracht« and to which Mozart had been introduced on the occasion of his father’s initiation. Just as the first part (nos. 1-8) is clearly based on Wieland’s fairly tales, parts 2-4 (nos. 9-30) are based on the mystery theory of the Freemasons and their primary source, Terrasson’s novel Sethos.